Pioneers of Modern Economics in Britain
XVI, 215 p.
Keywords: This volume contains a series of biographical essays on seven of the most influential economists in Britain since World War II. Each essay gives background details and a critical assessment of the economist's work, examining his or her impact on the development of modern economics.